Barriers of Accessing Elderly Care Services in Bangladesh - Masud, Rana (Magyar Gerontológia, 2023)
Approximately one in ten persons in Bangladesh is over 60 years old and it is estimated that this figure will increase to 21.5% in 2050. This huge proportion of the population often faces barriers in terms of accessing elderly care services.